Doyle Creek Land and Cattle Company - Judy Mills; Sara Dawson (Symphony in the Flint Hills, 2009)
Doyle Creek Land & Cattle Company is dedicated to improvement of the beef industry and is continually striving to achieve excellence in their commercial cow-calf operation. Located in the Flint Hills of Kansas, Doyle Creek consists of three ranches owned and operated by Randy and Judy (Strait) Mills and their two daughters. Mary and Frank
Keywords: ranches; farm; family; cattle; cow; calf; ecology; native; Flint Hills; grass; prairie; herd; historical; spring; business; Tourism